Francis Fukuyama dan “Berakhirnya Sejarah” seorang neokonservatif - Muhamad Takiyuddin Ismail, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
As a political economy scholar, Francis Fukuyama will always be remembered for “the end of history” thesis. He has made no secrets regarding his affiliation to neoconservatism and his close involvement in the implementation of the Pax Americana agenda through the Project for the New American Century. However, post-September 11, 2001 or widely known as 9/11, has led Fukuyuma to believe that the neoconservative approaches in the war against terrorism are flawed. This article tries to demonstrate the extent of Fukuyama’s disillusionments and his proposals to reinvigorate United States’ foreign policy in his new book, After the Neocons (2006). What seems clear is that Fukuyama still defends neoconservatism as a good approach. Should the idea of democratisation be perceived as effectively practised, the neoconservatives should pay more attention to the aspect of political development